Recommendations for interventional pulmonology during COVID-19 outbreak: a consensus statement from the Portuguese Pulmonology Society - Guedes, F (2020)
Coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by a novel SARS-CoV-2 pathogen. Its capacity for human-to-human transmission through respiratory droplets, coupled with a high-level of population mobility, has resulted in a rapid dissemination worldwide. Healthcare workers have been particularly exposed to the risk of infection and represent a significant proportion of COVID-19 cases in the worst affected regions of Europe. Like other open airway procedures or aerosol-generating procedures, bronchoscopy poses a significant risk of spreading contaminated droplets, and medical workers must adapt the procedures to ensure safety of both patients and staff. Several recommendation documents were published at the beginning of the pandemic, but as the situation evolves, our thoughts should not only focus on the present, but should also reflect on how we are going to deal with the presence of the virus in the community until there is a vaccine or specific treatment available. It is in this sense that this document aims to guide interventional pulmonology throughout this period, providing a set of recommendations on how to perform bronchoscopy or pleural procedures safely and efficiently.